ANALISIS PENGARUH VANE TERHADAP KARAKTERISTIK DOUBLE SLOTTED FLAP PESAWAT N2XX DENGAN METODE SIMULASI COMPUTATIONAL FLUID DYNAMIC - Mirna Sari; Gaguk J atisukamto; Gembong Djoni Putranto (ROTOR, 2017)
The stability of an airplane is influenced by aerodynamic characteristics, one of which is the lift coefficient (C). The value C is the ratio between the lift force (L) and the dynamic pressure (q). The value of C is determined based on the design of the airfoil shape and the use of the type of flap. The increase in C from the previous study using the simulation method obtained 20.4% with the addition of a flap. This study aims to simulate folds by adding vane (double slotted flap). The methodology in the study uses a simulation of Computational Fluid Dynamic (CFD). The research results of airfoils with the blade having a maximum C of 35.99% are higher than airfoil designs without vane, or 5.77 and 5.61 respectively. The maximum C value of an airfoil with vane or airfoil without using blade occurs at the angle of attack (α) = 16o. The research conclusion informs that vane influences the characteristics of the N2XX aircraft. Vane can minimize the occurrence of a stall (decrease in the value of C) of airplanes in take-off and landing conditions. Keywords: C, vane, double slotted flap, airfoil